Business plan for WasteNotMeal - Choo, Ching Yee (2019)
WasteNotMeals (WNM) is a for-profit social enterprise founded on the green philosophy of preservation and conservation of natural resources, in this case, saving and redistributing food that would have otherwise gone to waste due to normal business practises. The company aims to specifically help cooked food purveyors or restaurants sell off as much of their food as possible in order to tackle the mounting food wastage from the food industry stemming from this particular source. The main target would be the middle-income earners or higher or whoever could afford to eat out often, lack time to cook at home, and adventurous with their palate but could not sample outside food often due to prohibitive full prices of the meals. The idea is to sell these meals at a fraction of their usual prices but at off peak hours chosen by the food proprietors.